Physiological and biochemical responses of transgenic AtEXPA1 tobacco plants to drought stress - Abbas Nameni; Alireza Abbasi; Manizhe Sabokdast (تنش های محیطی در علوم زراعی, 2021)
Drought stress is one of the most destructive abiotic stresses. Expansins are one of the cell wall expandable proteins that can expand the cell wall under a pH-dependent pathway. Stomatal opening rate Due to the expression of AtEXPA1 gene in transgenic plants has been observed. In this study, second generation (T2) of three transgenic tobacco lines with AtEXPA1 gene were studied for some physiological and biochemical traits under drought stress. Transgenic lines includes 2, 4 and 7 and Non-transgenic commercial cultivar Samson as control were cultivated. RWCL and leaf chlorophyll content has been reduced under drought stress, and ELIL, Lipid peroxidation as MDAL and leaf proline content has been increase. The activity of antioxidant enzymes such as, catalase (CAT), guaiacol peroxidase (GPOX), ascorbate peroxidase (APOX) and polyphenol oxidase (PPO) was increased in leaves under drought stress. In this study, according to biochemical traits Line 2 and Line 7 and according to physiological traits Line4 in Compared to the control cultivar, could cope with stress and introduce as tolerate cultivars.